2009
DOI: 10.1177/0306624x09338379
|View full text |Cite
|
Sign up to set email alerts
|

Typology of Intimate Partner Homicide

Abstract: Fifteen inmates from Ayalon prison, a maximum-security prison in Israel, who were convicted of murder, attempted murder, or manslaughter of their female intimate partner, have participated in a study designed to examine integrated variables-personal, interpersonal, and environmental-familial-connected with this phenomenon. Analyses of the in-depth interviews demonstrate that despite the different motivations the perpetrators displayed with regard to the murder, they share some common themes. On the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
3
26
0
8
Order By: Relevance
“…Elisha et al, (2010) also identified three types of IPH through the qualitative assessment of 15 inmates in Israel (10 were convicted of murder, 3 of manslaughter, and 2 of attempted murder). In their typology, the betrayed husband killed his partner after discovering her ongoing sexual betrayal, which led to their family breakup; the abandoned obsessive lover murdered his intimate partner following her intention to leave him; and the tyrant murdered his intimate partner following an ongoing confrontation with her, which gradually escalated until he decided to kill her as a way of triumphing over her.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elisha et al, (2010) also identified three types of IPH through the qualitative assessment of 15 inmates in Israel (10 were convicted of murder, 3 of manslaughter, and 2 of attempted murder). In their typology, the betrayed husband killed his partner after discovering her ongoing sexual betrayal, which led to their family breakup; the abandoned obsessive lover murdered his intimate partner following her intention to leave him; and the tyrant murdered his intimate partner following an ongoing confrontation with her, which gradually escalated until he decided to kill her as a way of triumphing over her.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it would be interesting to analyze other variables in greater detail, for instance, the psychological profile by means of specific psychometric tools (e.g., for personality disorders) (Loinaz, Ortiz-Tallo, & Ferragut, 2012). These assessment limitations prevented us from analyzing typological proposals, as others have done (Dixon et al, 2008;Elisha et al, 2010). Recent studies (Debowska, Boduszek, Dhingra, Kola, & Meller-Prunska, 2015;Debowska, Boduszek, & Willmott, in press) also emphasize the weight of childhood exposure to violence in the development of cognitive distortions, and dating sexual violence-supportive attitudes among different types of offenders, including homicide offenders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pesar de la dificultad de la comparación entre los distintos estudios, por la disparidad en la metodología de investigación utilizada, los datos coinciden en señalar que el HCP es un fenómeno complejo y multidimensional (Dobash, Dobash, Cavanagh y Medina-Ariza, 2007; Johnson, Eriksson, Mazerolle y Wortley, 2017). En muchos casos no aparece un rastro de violencia anterior en la relación o signos de alteraciones psicológicas o conductuales en el homicida (Cobo, 2007;Contreras, 2014;Dutton y Kerry, 2002;Elisha, Idisis, Timor y Addad, 2010;Nicolaidis et al, 2003;Stith, Smith, Penn y Ward, 2004).…”
Section: El Modelo Ecológicounclassified